Othering in politics: how affective polarization undermines democratic philia? - Erdoğan, Emre; Uyan-Semerci, Pınar (Frontiers in Political Science, 2025)
Affective polarization, characterized by animosity and distrust between partisan groups, threatens democratic resilience and social cohesion by fostering social distance, moral superiority, and political intolerance. This study conceptualizes affective polarization as a form of othering that undermines Aristotle’s concept of philia—political friendship—essential for mutual respect and dialogue. Using survey data from 4,006 respondents in Türkiye, we measure dimensions of polarization, including aversion to social interactions with out-groups, stereotyping, and the denial of basic rights to perceived opponents. Results reveal entrenched divisions, with in-groups attributing positive traits to themselves while assigning negative characteristics to out-groups, reinforcing a “them versus us” mentality. To complement these findings, a field experiment examines participants’ emotional responses to politically charged scenarios involving global warming, bilingualism, and headscarves. Strong negative emotions, including anger and disgust, are directed toward out-groups, highlighting the visceral intensity of polarization and its role in deepening societal divides. By framing affective polarization within the theoretical lens of philia and othering, this study underscores its implications for democratic governance, emphasizing the need for strategies to rebuild trust, reduce hostility, and foster inclusive dialogue rooted in civic values.